P.010 Efficacy, safety, and tolerability of ubrogepant for the acute treatment of migraine: a single-attack phase 3 study, ACHIEVE II. (5th June 2019) - Lipton, RB; Dodick, DW; Ailani, J; Lu, K; Lakkis, H; Finnegan, M; Szegedi, A; Trugman, JM; Davidovic, G
Abstract : Background: To evaluate efficacy, safety, and tolerability of ubrogepant for acute treatment of migraine attacks.Methods: Multicenter, double-blind, phase 3 study (NCT02867709). Randomized patients (1:1:1, placebo or ubrogepant 25mg or 50mg) had 60 days to treat one migraine attack (moderate/severe pain intensity). Co-primary efficacy endpoints (2 hours post initial dose): headache pain freedom and absence of most bothersome migraine-associated symptom (MBS). Secondary endpoints: pain relief, sustained pain relief, sustained pain freedom, and absence of migraine-associated symptoms.Results: 1686 patients were randomized (safety population: n=1465; mITT population: n=1355). Mean age: 41 years; white: 81%; female: 89%. Significantly greater proportions of ubrogepant- than placebo-treated patients achieved 2-hour pain freedom (placebo: 14.3%; 25mg: 20.7%, adjusted P =0.0285; 50mg: 21.8%, adjusted P =0.0129) and absence of MBS for 50mg (placebo: 27.4%; 50mg: 38.9%, adjusted P =0.0129). Secondary endpoints (except absence of nausea at 2h) met statistical significance versus placebo for ubrogepant 50mg. Absence of MBS and secondary outcomes were not significant for 25mg after multiplicity adjustment. Ubrogepant's and placebo's AE profiles were similar.Conclusions: Co-primary endpoints were met for ubrogepant 50mg. Ubrogepant 25mg was significantly superior to placebo for 2h pain freedom. Ubrogepant was well tolerated. Results support the efficacy, tolerability, and safety of ubrogepant for acute treatment of migraine attacks.